Spawning Ecology and Spawning Site Fidelity of Alligator Gar, Atractosteus spatula, in the Fourche LaFave River: Implications for River-Floodplain Management and Alligator Gar Conservation - S. Reid Adams; Thomas E. Inebnit; Lindsey C. Lewis; Christopher J. Naus; Edward Kluender; Geoffry G. Spooner (Southeastern Fishes Council Proceedings, 2024)
We studied the spawning ecology of Alligator Gar, Atractosteus spatula, in the Fourche LaFave River (FLR) of Arkansas to better understand their reproductive ecology and spawning resource requirements. Evidence of spawning was only observed in floodplain tributary habitats, particularly the small, adventitious headwater stream West Fork Mill Creek (WFMC). A mid-May to mid-June spawning season was observed for Alligator Gar in the FLR that corresponded with rising water levels (mostly due to backflooding from the Arkansas River) and increased water temperatures (> 20°C). Direct spawning observations at WFMC were made on 17 June 2007, 15 June 2008, 23 May 2010, and 3 June 2013. Continued use of the same site indicates high spawning site fidelity. General spawning behavior was typical of gars consisting of circular swimming paths by groups, a lead individual (presumably a female) followed by males, and thrashing of shallow water as gametes were emitted. Eggs were mostly attached to herbaceous wetland vegetation, in particular Carex sp., at WFMC despite the presence of inundated shrubs, small trees, and nearby cropland during all years. Alligator Gar laid eggs in shallow water, often only 14 cm or less from the surface, and early larval stages were mostly sedentary, needing 8 days post spawn to reach a more active developmental stage. Eggs and larvae were highly vulnerable to lowering water levels, and we observed desiccation of eggs in some years. Floodplain tributaries functioned as both movement corridors and spawning and nursery habitat for Alligator Gar in the FLR riverscape. Maintaining passage within corridors connecting adult staging and spawning/rearing habitats is important for conservation. As an obligate spawner in open canopied, early successional floodplain habitats, Alligator Gar should be a focal species to ensure conservation programs include floodplain fish conservation, habitat heterogeneity, and availability of herbaceous wetland vegetation in their conservation objectives and goals rather than focusing merely on reforestation.
Keywords: Wetland Vegetation; Carex; Floodplain Tributary; Floodplain Restoration